KLAUSA RELATIF BAHASA INGGRIS DAN BAHASA INDONESIA: ANALISIS KONTRASTIF STRATEGI PERELATIFAN, FUNGSI, DAN KARAKTERISTIK ALAT PERELATIF (olish andlndonesianRelative Clause: Contrastive Analysis ofRelativisation Strategy, - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This research aims at identifying and comparing the function and cha¬racteristic of relative pronouns in English and the ligature yang in Indone¬sian, and also identifies and compares the relative clause strategy of both languages by using contrastive analysis. The research findings are explained by using the method of comparative description. The research then leads to the finding that both English and Indonesian have differences and similari¬ties in terms of relative clause construction. In English, the various relative pronouns fully have an argument status within relative clauses, meaning that these pronouns function as the substi¬tute of noun phrease (NP) elements which are in the position of object, direct object, and indirect object of a preposition within dependent clauses. Mean¬while, the ligature yang in Indonesian cannot have an argument status within relative clauses. This yang is more likely as a ligature